Views on ageing: a qualitative study among malay middle - aged women in urban setting in Malaysia - Minhat, Halimatus Sakdiah; Sulaiman, Hamizah; Mohd Zulkefli, Nor Afiah (The International Journal of Health Sciences and Research, 2015)
Introduction: Ageing is an inevitable process. Objective: This study aimed to explore the views of the middle-aged women on ageing. Methods: Focus group discussions (FGD) were conducted among 36 urbanized women aged between 35 and 59 years old, conducted for an average of 1 to 2 hours each. Respondents were selected using the maximum variation sampling involving five age categories which include 35 to 39, 40 to 44, 45 to 49, 50 to 54 and 55 to 59 years old. Results: The identified themes were concentrated on three main changes that occur with ageing process which were physical, emotional and hormonal changes which were frequently expressed and discussed among the younger age categories (35 to 49 years old). These were manifested as declining physical ability, healthy and changes in physical appearances (physical), having a more sensitive feeling, like attentions from others and the emotional change associated with having married children and grandchildren (emotion) and also menopausal symptoms (hormonal). Conclusion: The middle-aged women involved in this study perceived a person is said to be old once they experiencing physical, emotional and hormonal changes. They should be made aware of the possible changes associated with ageing and also the changes are part of normal process and should not be anxious or worried to go through the ageing process. The perceptions of the middle-aged women play an important role in preparing them to face the later life and also to ensure they are undergoing a successful and healthy ageing process.